Adaptación del arroz riego (oryza sativa l.) en el caribe (2011)
In Colombia, the rice crop under irrigation system ranks first in food security, economic value and employment offer among annual crops, becoming the most important. The objective of this study was to quantify increasing, stability and adaptability of irrigated rice in five departments of the Colombian Caribbean area. Data from the Ministry of Agriculture and Rural Development for the departments of Cordoba, Bolivar, Magdalena, Cesar and Guajira, during the year period 1987 to 2008 were used. The increasing in yield was determined using the linear regression analysis among years (independent variable) and grain yield (dependent variable) in each department. The yield stability was determined by the coefficient of variation across of three consecutive periods of five years and the last seven years. The yield adaptability was estimated using linear regression coefficient (bi). The results indicate that progress in grain yield in the Colombian Caribbean, ranged from 1.15% to 3.36% per year and 52.2 to 168.1 kg.ha-1, especially in the department of Bolívar (3.36% per year and 168.1 kg.ha-1). The yield stability was generally high (CV4.57) for grain yield.